A inserção das mulheres na Câmara Municipal de Natal (1988 - 2004) - Freire, Aluizia do Nascimento (2008)
This work has as objective to reflect about the insertion of the women in the City Council of Natal in the period from 1988 to 2004. We focused our discussion in the context of the politics of quota that has with objective to decrease the frame of inequalities existent between women and men in the politics, besides of to analyze which the determinants responsible for the women's sub-representation. The research still consists of an analysis of the councilor s women profile and how they were seen in that space of power. We analyzed our study object in a gender vision, since this is related intrinsically the social relationships and the relationships of power. The women, for a long time, they were excluded of the participation in the public life, being just seen as mere expectants. This research is informed mainly by studies which discuss the Gender (Scott, 1990), (Perrot, 1988), (Badinter, 1995), (Bruschini, 2002). We also analyzed the power, politics in the vision of Marx (1996), Foucault (1982) and (Arendt, 2001). We tried to analyze the women's presence in the spaces public and private, showing your conflicts and contradictions faced in the society, focalizing the political character of the women's inclusion in the spaces in that are inserted. The instrument of collection of data was the semi-structured questionnaire, descriptive and analytical - critical. The analyses of the interviews show to the sub-representation of women over the years as a determining factor for these women continue in the invisibility. The women were interviewed councillora ex- bounded from 1988 to 2004. The conclusion the one that we arrived is that this sub-representation has as decisive the patriarchal system that prevailed for a long time in our society and still dominates and affects women in all areas of your life. This becomes more serious in the capitalist society in which prevail the interests of those that it stops the produced wealth